Growth factor receptor binding protein 14 inhibition triggers insulin‐induced mouse hepatocyte proliferation and is associated with hepatocellular carcinoma. Issue 4 (21st February 2017) - Morzyglod, Lucille; Caüzac, Michèle; Popineau, Lucie; Denechaud, Pierre‐Damien; Fajas, Lluis; Ragazzon, Bruno; Fauveau, Véronique; Planchais, Julien; Vasseur‐Cognet, Mireille; Fartoux, Laetitia; Scatton, Olivier; Rosmorduc, Olivier; et al.
Abstract : Metabolic diseases such as obesity and type 2 diabetes are recognized as independent risk factors for hepatocellular carcinoma (HCC). Hyperinsulinemia, a hallmark of these pathologies, is suspected to be involved in HCC development. The molecular adapter growth factor receptor binding protein 14 (Grb14) is an inhibitor of insulin receptor catalytic activity, highly expressed in the liver. To study its involvement in hepatocyte proliferation, we specifically inhibited its liver expression using a short hairpin RNA strategy in mice. Enhanced insulin signaling upon Grb14 inhibition was accompanied by a transient induction of S‐phase entrance by quiescent hepatocytes, indicating that Grb14 is a potent repressor of cell division. The proliferation of Grb14‐deficient hepatocytes was cell‐autonomous as it was also observed in primary cell cultures. Combined Grb14 down‐regulation and insulin signaling blockade using pharmacological approaches as well as genetic mouse models demonstrated that Grb14 inhibition–mediated hepatocyte division involved insulin receptor activation and was mediated by the mechanistic target of rapamycin complex 1–S6K pathway and the transcription factor E2F1. In order to determine a potential dysregulation in GRB14 gene expression in human pathophysiology, a collection of 85 human HCCs was investigated. This revealed a highly significant and frequent decrease in GRB14 expression in hepatic tumors when compared to adjacent nontumoral parenchyma, with 60% of the tumors exhibiting a reduced Grb14 mRNA level. Conclusion : Our study establishes Grb14 as a physiological repressor of insulin mitogenic action in the liver and further supports that dysregulation of insulin signaling is associated with HCC. (Hepatology 2017;65:1352‐1368).